2016
DOI: 10.1002/elps.201600310
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and electrokinetic motion of electrically anisotropic Janus droplets in microchannels

Abstract: StatementThis is the peer reviewed version of the following article: Li, M. and Li, D. (2017), Fabrication and electrokinetic motion of electrically anisotropic Janus droplets in microchannels. ELECTROPHORESIS, 38: 287-295. doi:10.1002/elps.201600310, which has been published in final form at http://dx.doi.org/10.1002/elps.201600310. This article may be used for noncommercial purposes in accordance with Wiley Terms and Conditions for Self-Archiving. 2 AbstractThis paper presents experimental investigations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…Janus droplets with precise size and topology are synthesized one by one in a droplet microfluidic system by shearing two parallel streams of immiscible phases with a continuous phase. Apart from the two above-mentioned methods, it has been reported that the generation of electrically induced Janus droplets (EIJDs) was conducted by using a direct current (DC) electrical field to induce the redistribution of positively charged aluminum oxide (Al 2 O 3 ) nanoparticles adhering on the surface of oil droplets in water. , As the Al 2 O 3 nanoparticles and the oil–water interface carry surface charges of opposite signs, the EIJDs fabricated with this method are optically and electrically heterogeneous between the two hemispheres.…”
Section: Introductionmentioning
confidence: 99%
“…Janus droplets with precise size and topology are synthesized one by one in a droplet microfluidic system by shearing two parallel streams of immiscible phases with a continuous phase. Apart from the two above-mentioned methods, it has been reported that the generation of electrically induced Janus droplets (EIJDs) was conducted by using a direct current (DC) electrical field to induce the redistribution of positively charged aluminum oxide (Al 2 O 3 ) nanoparticles adhering on the surface of oil droplets in water. , As the Al 2 O 3 nanoparticles and the oil–water interface carry surface charges of opposite signs, the EIJDs fabricated with this method are optically and electrically heterogeneous between the two hemispheres.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the motion mechanism of the interfacial particle in their study is different from that in this work. Li and Li , experimentally found that positively charged nanoparticles absorbed at an oil droplet surface move toward the negative electrode of the DC electric field and congregate on one side of the droplet but did not discuss the effect of the interface electrokinetic phenomenon on the particle motion in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, many functional PCs with PBGs have been fabricated with e-beam lithography [13,14], chemical vapour deposition [15], and interface selfassembly and templates [16][17][18][19]. Besides, coalescences of different liquids were also applied in the presence of an external electric field [20][21][22][23][24], magnetic field [25], high energy mixing [26][27][28][29], and immiscible droplets [8,[30][31][32]. Gu reported a kind of magnetic PC with anisotropic structural color via microfluidic emulsification and achieved controllable movement under magnetic fields [33].…”
Section: Introductionmentioning
confidence: 99%